A multirate controller-observer scheme for fully automatic vehicle control. (2015) - Fernando, W.U.N.; Kumarawadu, Sisil
Magnetic marker-based vehicular positioning systems encounter the issue of speed dependent sampling rates. This paper considers multirate vehicle control design for such intelligent vehicle highway systems (IVHSs). The discrete-time version of the IVHS vehicle model is utilised for control and observer synthesis. The lateral and longitudinal speed and position control is realised via state feedback design. The sampling of the magnetic markers is represented in a generic format such that multiple vehicle-mounted sensor-arrays can be incorporated for increased performance, partial redundancy, and higher sensor-fault tolerance. The observer design is presented in the form of time-varying gain Kalman observer. Simulation studies are performed for the comparison of the systems with and without the multirate observer. An IVHS with a 6 m magnetic maker spacing is simulated and is shown that the lateral control with the multirate observer performs with superior stability and accuracy compared with a system without the multirate observer.